2018
DOI: 10.3174/ajnr.a5644
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Outcomes of Endovascular Treatment within 24 Hours in Patients with Mild Ischemic Stroke and Perfusion Imaging Selection

Abstract: BACKGROUND AND PURPOSE: Endovascular thrombectomy has been accepted as the standard of care for patients with acute ischemic stroke. Our aim was to investigate the clinical outcomes of patients with mild ischemic stroke with acute proximal large-vessel occlusion after endovascular treatment within 24 hours of symptom onset.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 27 publications
0
7
0
Order By: Relevance
“…Prior retrospective analyses of patients with mildly symptomatic AIS due to LVO have found similar rates of good clinical outcomes between patients following MM or ET with 64-75% of patients living independently at 90 days and symptomatic ICH in 6-17% of patients. [6][7][8][9][10]17 A multicenter analysis has suggested that ET may be performed safely in these patients and may lead to improved outcomes over medical therapy. 11 However, the study utilized heterogenous pretreatment imaging criteria and is confounded by the inclusion of different treatment arms between different centers.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Prior retrospective analyses of patients with mildly symptomatic AIS due to LVO have found similar rates of good clinical outcomes between patients following MM or ET with 64-75% of patients living independently at 90 days and symptomatic ICH in 6-17% of patients. [6][7][8][9][10]17 A multicenter analysis has suggested that ET may be performed safely in these patients and may lead to improved outcomes over medical therapy. 11 However, the study utilized heterogenous pretreatment imaging criteria and is confounded by the inclusion of different treatment arms between different centers.…”
Section: Discussionmentioning
confidence: 99%
“…However, these prior studies suffer from heterogeneity in pre-treatment imaging, variability in triage with perfusion imaging, and comparisons between ET and medical management (MM) groups between different centers. [6][7][8][9][10][11][12]…”
Section: Introductionmentioning
confidence: 99%
“…All eligible subjects were divided into the MET group or the medical group, according to whether MET was performed. The MET group included the initial MET and rescue MET [13]. The local Ethics Committees of each center approved the use of patients’ data for this study, and written consents of the patients were waived due to its retrospective nature.…”
Section: Methodsmentioning
confidence: 99%
“…For patients who are beyond the IVT treatment window, Shang et al demonstrated that EVT in patients with a low NIHSS score is feasible up to 24 hours following symptom onset; however, there was no functional improvement observed with EVT. 51 Robust collateral status has been correlated with reduced infarct expansion and favorable outcomes in LVO-AIS. 61 It is likely that low patients with LVO and a low NIHSS score with poor collateral status are more susceptible to END.…”
Section: Evt Patient Selectionmentioning
confidence: 99%